2009
DOI: 10.1128/mcb.00370-09
|View full text |Cite|
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor β/δ (PPARβ/δ) but Not PPARα Serves as a Plasma Free Fatty Acid Sensor in Liver

Abstract: Peroxisome proliferator-activated receptor ␣ (PPAR␣) is an important transcription factor in liver that can be activated physiologically by fasting or pharmacologically by using high-affinity synthetic agonists. Here we initially set out to elucidate the similarities in gene induction between Wy14643 and fasting. Numerous genes were commonly regulated in liver between the two treatments, including many classical PPAR␣ target genes, such as Aldh3a2 and Cpt2. Remarkably, several genes induced by Wy14643 were upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 70 publications
3
120
0
2
Order By: Relevance
“…Depending on the type of tissue involved, the effect of fatty acids on ANGPTL4 mRNA can be mediated by different PPAR isotypes ( 18 ). Recently it was shown that PPAR ␦ , but not PPAR ␣ , serves as a plasma FFA sensor in the liver ( 19 ). Krey et al ( 20 ) showed that the affi nity of PPAR ␦ for linoleic acid is higher than for oleic acid, and that 8(S)-HETE (an arachidonic acid metabolite), linolenic, and linoleic acids are the most potent natural ligands for PPAR ␦ .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the type of tissue involved, the effect of fatty acids on ANGPTL4 mRNA can be mediated by different PPAR isotypes ( 18 ). Recently it was shown that PPAR ␦ , but not PPAR ␣ , serves as a plasma FFA sensor in the liver ( 19 ). Krey et al ( 20 ) showed that the affi nity of PPAR ␦ for linoleic acid is higher than for oleic acid, and that 8(S)-HETE (an arachidonic acid metabolite), linolenic, and linoleic acids are the most potent natural ligands for PPAR ␦ .…”
Section: Resultsmentioning
confidence: 99%
“…Activation with the synthetic PPARd agonist GW501516 decreases plasma TAG and plasma FFA in dyslipidaemic subjects with central obesity (Ooi et al 2011). PPARd appears to sense and respond to elevated FFA by up-regulating genes such as Lipin 2 (Sanderson et al 2009), and in mice models PPARd agonists have previously been shown to protect against weight gain, steatosis, reduced HDL levels and elevated TAG levels, while PPARd null mice were more susceptible to weight gain (Barish et al 2006). This collectively suggests that activation of PPARd protects against obesity and/or dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of selected genes involved in lipid uptake, transport, lipolysis, de novo lipogenesis and fatty acid oxidation were analysed (Table 2). Additionally, we analysed the expression of the transcription factors PPARd and LXRa which have been described as fatty acid sensors regulating genes involved in lipid metabolism (Sanderson et al 2009;Strable and Ntambi 2010). Whereas there were no differences in PBMC gene expression levels of UCP2, HSL and PPARd between normal weight and MHO subjects, ARO subjects had significantly lower expression levels of these genes compared with both normal weight subjects (P = 0.041, P = 0.035 and P = 0.05, respectively) and MHO subjects (P = 0.003, P = 0.003 and P = 0.006, respectively) (Fig.…”
Section: Pbmc Gene Expressionmentioning
confidence: 99%
“…Studies have identified many ligands that activate and modulate PPAR functions (Berger et al, 1999;Forman et al, 1995;Itoh et al, 2008;Kliewer et al, 1997;Sanderson et al, 2009;Varga et al, 2011). These ligands are summarized in Table 1.…”
Section: Ppar Ligandsmentioning
confidence: 99%